Occupational Health Problems of Industrial Workers in Nsukka L.GA. of Enugu State: A paper presented at the 8th National Health Promotion Research Association of Nigeria (HEPRAN) Conference. Held at the Faculty of Education Auditorium, UNN, from the 12thto 15th October, 2011. - Ogbuji, Dr. (Mrs) C.N.; lwuagwu, T.Emmanuel (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This study was embarked on tofind out the occupational health problems of industrial workers in Nsukka LGA. The cross-sectional survey research design was adopted and four research questions and one hypothesis guided the study. The population consisted of 1040 people working in the industries. The multi-stage sampling procedure was used to select a sample of one hundred and seventy two senior and junior industrial workers that were used for the study. The instrument for data collection was a questionnaire which was validated by three experts in research work and the reliability was also determined. The data was analyzed using frequencies and percentages and the hypothesis was verified using chi-square (X^2) statistic. The following major findings emerged: Industrial workers in Nsukka experienced a lot of health problems. These health problems cut across the three dimensions of health which are physical, social and emotional. The study showed that the commonest health problems were injuries, poor wages and lack of incentives and self-destruction behaviours such as drinking, smoking, among others. It was then recommended that employers and employees should adhere strictly to the ILO safety rules and work conditions in order to enhance their health status and also increase their productivity.